Increased fractalkine expression in placental tissue and HUVECs from pregnant women with gestational diabetes mellitus and its correlation with clinicopathological variables in a case-control study - Akin Usta; Ceyda Sancakli Usta; Duygu Lafci; Cevahir Tekcan; Gülay Turan (The Journal of Maternal-Fetal & Neonatal Medicine, 2025)
Aim Gestational diabetes mellitus is defined as any glucose intolerance that begins during pregnancy, and it is one of the most common metabolic disorders complicating pregnancies, affecting approximately 10–14% of all pregnancies. Maternal carbohydrate metabolism changes during pregnancy to ensure adequate nutrition for the fetus, with the human umbilical vein and the placenta being important regulators of this physiological state. This study aimed to evaluate fractalkine (FKN) immunoreactivity in GDM pregnancies and its association with maternal/fetal health outcomes.Methods In this case-control study, a total of 89 pregnant women (44 GDM and 45 non-GDM) underwent a 50 g glucose loading test (GCT) between 24 and 28 weeks of gestation. GCT cutoff value was chosen as <140 mg/dl. Women with high GCT values underwent rapid diagnostic testing with a 3-hour glucose tolerance test (GTT). Placenta samples were obtained after cesarean section. Immunohistochemistry for FKN was performed on formalin-fixed and paraffin-embedded sections. Finally, the relationship between FKN expression and clinical manifestations of GDM was evaluated.Results FKN expression was significantly different between pregnant women with and without GDM. Specifically, FKN expression was increased in the capillary endothelium (p < 0.0001) and human umbilical vein endothelial cells (HUVECs) (p = 0.0011) in pregnant women with GDM compared to those without GDM. Furthermore, FKN expression in HUVECs was found to be associated with fetal macrosomia (p = 0.0099) and neonatal hypoglycemia (p = 0.0291). Additionally, FKN expression in the capillary endothelium was found to be associated with preeclampsia (p = 0.0250). Regarding the pathological changes of the placenta with FKN expression, significant correlations were identified with both capillary endothelial FKN expression and HUVEC FKN expression.Conclusions The observed differences suggest a potential association between the immunohistochemical expression of FKN and the presence of GDM, placental changes, and adverse outcomes of pregnancy.